2020
DOI: 10.1097/jpn.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Case Reports of Poor Neonatal Outcomes With Water Immersion During Labor and Birth

Abstract: Water immersion is a valuable comfort measure in labor, that can be used during the first or second stage of labor. Case reports of adverse outcomes create suspicion about water birth safety, which restricts the availability of water birth in the United States. The objective of this study was to synthesize the information from case reports of adverse water birth events to identify practices associated with these outcomes, and to identify patterns of negative outcomes. The research team conducted a systematic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…A review of case reports of poor newborn outcomes found that when reported, cord avulsion was easily managed by the midwife with no consequences for the newborn. 75 Our results show that water immersion has the potential to make a meaningful contribution to the global agenda towards promoting physiological birth. [76][77][78][79][80] Labouring and/or giving birth in water can reduce maternal pain with no increased risk of an adverse event, and without the risk introduced by epidural and opioids.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A review of case reports of poor newborn outcomes found that when reported, cord avulsion was easily managed by the midwife with no consequences for the newborn. 75 Our results show that water immersion has the potential to make a meaningful contribution to the global agenda towards promoting physiological birth. [76][77][78][79][80] Labouring and/or giving birth in water can reduce maternal pain with no increased risk of an adverse event, and without the risk introduced by epidural and opioids.…”
Section: Discussionmentioning
confidence: 85%
“…A review of case reports of poor newborn outcomes found that when reported, cord avulsion was easily managed by the midwife with no consequences for the newborn. 75 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of neonatal sepsis is often cited by those who oppose WWI/Waterbirth (15) . However, case reports of neonates infected with L. pneumophila and P. aeruginosa (16) , appear to have resulted from a deviation from established waterbirth protocols and the use of unclean water. Overwhelmingly, recent literature suggests no increase in infective sequalae from WWI/WB, which is consistent with our findings (17,18) .…”
Section: Resultsmentioning
confidence: 99%
“…The risk of neonatal sepsis is often cited by those who oppose WWI/waterbirth 16 . However, case reports of neonates infected with Legionella pneumophila and Pseudomonas aeruginosa 17 appear to have resulted when a deviation from established waterbirth protocols had occurred or from the use of unclean water. Overwhelmingly, recent literature suggests no increase in infective sequalae from WWI/waterbirth 18,19 …”
Section: Discussionmentioning
confidence: 99%